2009
DOI: 10.1080/14756360802334800
|View full text |Cite
|
Sign up to set email alerts
|

CD26/DPPIV cell membrane expression and DPPIV activity in plasma of patients with acute leukemia

Abstract: CD26/DPPIV (dipeptidil peptidase IV) displays an array of diverse functional properties, with a role in the development of several human cancers. This enzyme is found mainly anchored in the membrane of cells although it also has an enzymatically active plasma isoform. The regulation of biological activities of cytokines by DPP IV activity has a potential role in the homeostatic regulation of hematopoiesis. In this study, we analyzed the CD26 antigen cell membrane expression by flow cytometry and the DPPIV acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In contrast, DPP4 also appears to have an important role in the development of selected haematological malignancies (Farag et al ., ). Higher levels of DPP4 are expressed in chronic lymphocytic leukaemia B cells compared with their normal resting B cell counterparts (de Andrade et al ., ). In addition, DPP4 expression is mainly found in aggressive subtypes of non‐Hodgkin lymphoma, such as T cell lymphoblastic lymphoma (T‐LBL)/T cell acute lymphoblastic leukaemia (T‐ALL) and T cell CD30+ anaplastic large cell lymphoma (Ribatti et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, DPP4 also appears to have an important role in the development of selected haematological malignancies (Farag et al ., ). Higher levels of DPP4 are expressed in chronic lymphocytic leukaemia B cells compared with their normal resting B cell counterparts (de Andrade et al ., ). In addition, DPP4 expression is mainly found in aggressive subtypes of non‐Hodgkin lymphoma, such as T cell lymphoblastic lymphoma (T‐LBL)/T cell acute lymphoblastic leukaemia (T‐ALL) and T cell CD30+ anaplastic large cell lymphoma (Ribatti et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Patients with B-cell chronic lymphocytic leukemia had elevated mRNA and protein levels of DPP8 and DPP9; 35 plasma DPP activity was elevated in 80 and 62% in patients with lymphoid leukemia and AML, respectively. 36 These elevated DPP levels suggest these enzymes may have a role in leukemia pathogenesis, and are thus valuable therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that CD26 plays a regulatory role in the neoplastic transformation and progression of various types of tumours, and it may also play a role in tumour migration and metastasis as a result of its ability to bind extracellular matrix proteins [1,2]. It is thought that CD26 plays an important role in hematological malignancies, mainly in aggressive subtypes of T-cell non-Hodgkin lymphoma in which it is highly expressed by neoplastic cells [3,4]. Although CD26 expression is very low in B-cells, it is greatly up regulated following activation [5].…”
Section: Introductionmentioning
confidence: 99%